Partition Efficiency of High-Pitch Locular Multilayer Coil for Countercurrent Chromatographic Separation of Proteins Using Small-Scale Cross-Axis Coil Planet Centrifuge and Application to Purification of Various Collagenases with Aqueous-Aqueous Polymer Phase Systems - Shinomiya, Kazufusa (2011)
Partition efficiency of the high-pitch locular multilayer coil was evaluated in countercurrent chromatographic (CCC) separation of proteins with an aqueous-aqueous polymer phase system using the small-scale cross-axis coil planet centrifuge (X-axis CPC) fabricated in our laboratory. The separation column was specially made by high-pitch (ca 5 cm) winding of 1.0 mm I.D., 2.0 mm O.D. locular tubing compressed at 2 cm intervals with a total capacity of 29.5 mL. The protein separation was performed using a set of stable proteins including cytochrome C, myoglobin, and lysozyme with the 12.5% (w/w) polyethylene glycol (PEG) 1000 and 12.5% (w/w) dibasic potassium phosphate system (pH 9.2) under 1000 rpm of column revolution. This high-pitch locular tubing yielded substantially increased stationary phase retention than the normal locular tubing for both lower and upper mobile phases. In order to demonstrate the capability of the high-pitch locular tubing, the purification of collagenase from the crude commercial sample was carried out using an aqueous-aqueous polymer phase system. Using the 16.0% (w/w) PEG 1000 – 6.3% (w/w) dibasic potassium phosphate – 6.3% (w/w) monobasic potassium phosphate system (pH 6.6), collagenase I, II, V and X derived from Clostridium hystolyticum were separated from other proteins and colored small molecular weight compounds present in the crude commercial sample, while collagenase N-2 and S-1 from Streptomyces parvulus subsp. citrinus were eluted with impurities at the solvent front with the upper phase. The collagenase from C. hystolyticum retained its enzymatic activity in the purified fractions. The overall results demonstrated that the high-pitch locular multilayer coil is effectively used for the CCC purification of bioactive compounds without loss of their enzymatic activities.